Zeichentragende Artefakte im sakralen Raum. Zwischen Präsenz und UnSichtbarkeit - Theis, Christoffer; Willer, Laura; Kiyanrad, Sarah; Keil, Wilfried E. (De Gruyter, 2019)
Sign-bearing artifacts are immanent elements of sacred spaces in many cultures. Often, one encounters a phenomenon there that might be described as deliberate invisibility, the conscious concealment of artefacts and writing. The volume examines this interplay of presence and invisibility using the example of sign-bearing artefacts in sacral spaces in various religions in the Near East and Europe.
English
German
Keywords: Visibility sacred space presence writing